PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SD NEGERI 27 SUNGAI SAPIH - Siti Nurhasanah; Rahmia Tulljanah, Ade Irma Suryani; Annisa Kharisma, Alfroki Martha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of Pancasila Education of fourth grade students of SDN 27 Sungai Sapih. This is caused by the learning process has not been running effectively due to the lack of variety of interesting learning models and low participation and interaction between students in the learning process. The purpose of this study was to prove the effect of the Think Pair Share (TPS) type cooperative learning model on students' cognitive learning outcomes in Pancasila education learning in class IV of SD Negeri 27 Sungai Sapih. The research method used is Quasi Experimental Design with Nonequivalent Posttest-Only Control Group Design. The population in this study were all grade IV students of SDN 27 Sungai Sapih as many as 49 students consisting of two classes, namely classes IV A and IV B. The sampling technique used saturated sampling technique, which class IV A as an experimental class using the Think Pair Share (TPS) Cooperative Learning Model, while class IV B as a control class. The data collection technique in this study used a test in the form of multiple choice questions totaling 20 items. Based on the results of data analysis, the data from both sample classes were normally distributed and homogeneous. The posttest results showed that the experimental class average of 82.69 was higher than the control class of 73.7. Based on the results of the hypothesis, it can be seen that tcount = 3.125 > ttable = 1.667 with a significant level of 5%, so the hypothesis H1 is accepted and H0 is rejected. The conclusion of this study is that the Think Pair Share (TPS) type cooperative learning model has an influence on students' cognitive learning outcomes in Pancasila education learning in class IV SDN 27 Sungai Sapih.